ØªØ£Ø«ÙŠØ± Ø§Ø³ØªØ±Ø§ØªÙŠØ¬ÙŠØ© ØªÙˆØ¬ÙŠÙ‡ Ø§Ù„ØªÙÙƒÙŠØ± Ø®Ù„Ø§Ù„ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© ÙÙŠ ØªÙ†Ù…ÙŠØ© Ø§Ù„ÙÙ‡Ù… Ø§Ù„Ù‚Ø±Ø§Ø¦ÙŠ Ù„Ø¯Ù‰ Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ø¹Ø§Ù„ÙŠØ© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© Ø§Ù„ØÙƒÙˆÙ…ÙŠØ© Ù¡ Ø¨Ø§Ø¯Ù†Ø¬ Ø¨Ø§Ù†Ø¬Ù†Ø¬ - Bungsu, Linori Putri; Aisyah, Devy; Amelia, Amelia (IAIN Batusangkar, Indonesia, 2020)
This research aims to analyze the influence of Directed Reading Thinking Activity (DRTA) strategy on reading comprehension of Arabic language at MAN I Padang Panjang. The researcher used experimental research. The design was post-test onlyÂ control groupÂ of true-experimental design. Technique of data collection is reading test and then analyzed by using t-test. After DRTA strategy was implemented in experimental group, while control group was taught using conventional method, it was obtained that the mean score of the experimental group was 90.92 and the mean score of control class was 70.36. Then, by using t-test, it was found that tcalculated is higher than ttable, 10,82>2,682. It means that Ho is rejected and Ha is accepted. It can be concluded that DRTA strategy influences studentsâ€™ reading comprehension in Arabic language.